Constitutional Provisions for Social Justice in India and its Critical Evaluation in Panchayat Raj Institutions (ISJN Journal, 2022)
In India, the village is the most important social unit. More than Sixty per cent of the Indian population still resides in rural areas. In rural areas, Panchayat Raj Institutions (PRI) play a vital role in protecting social justice the present study was carried out to assess protection of social justice through Panchayat Raj Institutions. The study has adopted exploratory research design to narrate the qualitative data from Panchayat elected members. The data was collected through focused group discussions (FGD) with Panchayat elected members by posing questions and facilitating to have discussion about social justice protection through Panchayat Raj Institutions of three village Panchayats in the Bangalore rural district. From this study it was found that, elected members from Scheduled Castes, Scheduled Tribes, and Women, the political assertion is lagging. Though the Panchayat Raj is a decent mechanism for rural India, many difficulties exist, such as lack of leadership qualities, decision-making skill, assertiveness, nepotism, vested interests, power abuse, and so on… by panchayat elected members. To address these issues policy need to formulate to train and develop assertiveness among women and marginalized community members by giving proper training and education about Panchayat Raj system.